BRIDGING THE DIGITAL DIVIDE IN EDUCATION: A SYSTEMATIC REVIEW (SLR-PRISMA) OF DIGITAL INCLUSION STRATEGIES - Hanny Widya Fatmawati; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study examines the management of sports extracurricular activities as a strategic medium for students' mental refreshment during intensive Al-Qur'an memorization programs. The background of this research is based on the phenomenon of high cognitive load and the risk of psychological burnout faced by students in tahfidz-based Islamic educational institutions. Such conditions require a management system capable of balancing spiritual demands with mental health and physical fitness. This study aims to describe in-depth the management processes, including synchronous schedule planning, resource organization, implementation of contextual sports activities, and the evaluation of students' mental readiness. Using a library research method with a qualitative approach, the results indicate that well-structured extracurricular management functions as a stress-relief medium and concentration enhancer. Through POAC management functions (Planning, Organizing, Actuating, and Controlling), sports are proven to provide positive impacts on emotional stability, which supports memorization success. Overall, harmoniously integrated curriculum management significantly supports the holistic development of students in both physical and spiritual aspects.